2020
DOI: 10.1136/bmjopen-2019-035663
|View full text |Cite
|
Sign up to set email alerts
|

Health, illness and healthcare-seeking behaviour of the street dwellers of Dhaka City, Bangladesh: qualitative exploratory study

Abstract: ObjectiveThis study explored the illness experiences and healthcare-seeking behaviour of a cross-section of street dwellers of Dhaka City for designing a customised intervention.DesignA qualitative exploratory study of a sample of street dwellers of Dhaka City.SettingSamples were taken from three purposively selected spots of Dhaka City with a high concentration of the target population.ParticipantsFifteen in-depth interviews and six informal group discussions with 40 street dwellers (≥18 years), and key infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 13 publications
0
5
0
3
Order By: Relevance
“…The finding of our study about the epidemiological experiences of the street children is consistent to other related studies. Related studies (Eshita, 2018;Nazrin et al, 2020;Uddin et al, 2009;Ali & de Muynck, 2005), for instance, found that most of the street children were suffering from different types of diseases, including skin diseases, accidental injuries, hepatitis, fever, respiratory diseases, sexually transmitted infections, and warm infestations. Chowdhury et al (2017) associated street children's exposure to various skin disease and other communicable infections with their overall living conditions such as overcrowded living situations, unhealthy sleeping area, irregular bath, and less changing of clothes.…”
Section: Discussionmentioning
confidence: 99%
“…The finding of our study about the epidemiological experiences of the street children is consistent to other related studies. Related studies (Eshita, 2018;Nazrin et al, 2020;Uddin et al, 2009;Ali & de Muynck, 2005), for instance, found that most of the street children were suffering from different types of diseases, including skin diseases, accidental injuries, hepatitis, fever, respiratory diseases, sexually transmitted infections, and warm infestations. Chowdhury et al (2017) associated street children's exposure to various skin disease and other communicable infections with their overall living conditions such as overcrowded living situations, unhealthy sleeping area, irregular bath, and less changing of clothes.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, previous studies have indicated that, for disadvantaged people such as street dwellers, the first point of access to healthcare services is commonly at drug-retail outlets rather than at healthcare facilities. 32 34 Additionally, as previous observations indicated, in Ethiopia, most community drug-retail outlets do not follow regulations for dispensing medications, which allows and supports people in accessing drugs easily without a prescription, thus increasing the rate of self-medication use. 28 , 35 The prevalence of self-medication use in our study was comparable to that in a study conducted amongst college students in urban areas of the Amhara region, which is unsurprising as urban living is associated with self-medication practices.…”
Section: Discussionmentioning
confidence: 99%
“…8 As street dwellers are highly affected by low socioeconomic conditions and poor personal and environmental hygiene, they are the most disadvantaged and marginalized communities in urban areas. 9 Furthermore, given their overall low levels of living standards and the financial and time constraints linked to their livelihoods, street dwellers have limited access to conventional healthcare services or formal clinics for family planning and reproductive health services, 10 and are therefore extremely likely to self-medicate. Self- medication is the use of medication for self-treatment without visiting a healthcare provider for a prescription or diagnosis or to monitor the course of therapy.…”
Section: Introductionmentioning
confidence: 99%
“…As populações marginalizadas são aquelas que são socialmente excluídas com base em idade, raça, etnia, sexo, estado de deficiência, situação de migração geográfica, resultando na privação de receber serviços, incluindo serviços de saúde (...) 15…”
Section: Mulheres Em Situação De Rua E O Acesso à Saúdeunclassified